GP led medical student visits to primary schools can provide a valuable learning experience for both students and pupils. Issue 6 (2nd November 2021) - Macleod, David; Wass, Val; Laird, Shirley; McKeown, John
ABSTRACT: Background : A key clinical skill for undergraduate medical students is communication with children, yet it is becoming increasingly difficult for medical schools to provide sufficient experience within a secondary care setting. One potential solution to this is to develop innovative ways of involving local schools.Aim : To demonstrate what was learned from a pilot school visit and show how this was developed into a successful programme.Method : As part of their GP-based Foundations of Primary Care course, medical students were allocated to local primary schools in their tutorial groups led by their GP tutors. They developed and delivered health promotion activities that were appropriate for school pupils. Review of the visit identified areas of improvement which were used to redesign the programme. Surveys were conducted after the subsequent visit to assess the response of medical students, school pupils and teachers.Learning outcomes : Medical students gained experience in communicating and interacting with school-aged children, and developed teaching and team working skills. School pupils reported change in their health-related knowledge and behaviour and the visits introduced them to the medical profession at a young age. The visits were well received by the teachers who valued the medical students' input.Conclusions : Building on the learning from the pilot school visit, a successful programme was developed that was challenging but ultimately enhanced medical student learning and brought significant benefits for the school pupils. Future developments include the potential to expand the topics taught and developing training in teaching for medical students.